Analisis Pengaruh CAR, FDR, ROA, dan Inflasi Terhadap Non Performing Financing pada Bank Muamalat Indonesia - Ziana Azizah; Benny Barnas; Fatmi Hadiani (Journal of Applied Islamic Economics and Finance, 2022)
This research aims to see and analyze the influence of Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), Return on Asset (ROA), and Inflation on Non Performing Financing at Bank Muamalat Indonesia partially or simultaneously. This research uses secondary data in the form of quarterly report of Bank Muamalat Indonesia period 2012-2019 and statistical data from Bank of Indonesia. The method used in this research is multiple linear regression analysis. The result showed that CAR, FDR, ROA, and Inflation simultaneously have a significant effect on Non Performing Financing. Partially, CAR, FDR, and Inflation have no significant effect on Non Performing Financing. While the ROA variable has a significant effect on Non Performing Financing.